Non‐target effects of fungicides on nectar‐inhabiting fungi of almond flowers. Issue 2 (20th January 2017) - Schaeffer, Robert N.; Vannette, Rachel L.; Brittain, Claire; Williams, Neal M.; Fukami, Tadashi
Summary: Nectar mediates interactions between plants and pollinators in natural and agricultural systems. Specialized microorganisms are common nectar inhabitants, and potentially important mediators of plant‐pollinator interactions. However, their diversity and role in mediating pollination services in agricultural systems are poorly characterized. Moreover, agrochemicals are commonly applied to minimize crop damage, but may present ecological consequences for non‐target organisms. Assessment of ecological risk has tended to focus on beneficial macroorganisms such as pollinators, with less attention paid to microorganisms. Here, using culture‐independent methods, we assess the impact of two widely‐used fungicides on nectar microbial community structure in the mass‐flowering crop almond ( Prunus dulcis ). We predicted that fungicide application would reduce fungal richness and diversity, whereas competing bacterial richness would increase, benefitting from negative effects on fungi. We found that fungicides reduced fungal richness and diversity in exposed flowers, but did not significantly affect bacterial richness, diversity, or community composition. The relative abundance of Metschnikowia OTUs, nectar specialists that can impact pollination, was reduced by both fungicides. Given growing recognition of the importance of nectar microorganisms as mediators of plant‐pollinator mutualisms, future research should consider the impact of management practices on plant‐associated microorganisms and consequences for pollination services in agricultural landscapes.